2023
DOI: 10.3389/fnmol.2023.1163981
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin externalization mediates prion protein (PrP) peptide 106–126-associated mitophagy and mitochondrial dysfunction

Dongming Yang,
Jie Li,
Zhiping Li
et al.

Abstract: Proper mitochondrial performance is imperative for the maintenance of normal neuronal function to prevent the development of neurodegenerative diseases. Persistent accumulation of damaged mitochondria plays a role in prion disease pathogenesis, which involves a chain of events that culminate in the generation of reactive oxygen species and neuronal death. Our previous studies have demonstrated that PINK1/Parkin-mediated mitophagy induced by PrP106−126 is defective and leads to an accumulation of damaged mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…For silencing experiments, Lipofectamine RNAiMAX was used per manufactures' instructions for an siRNA final concentration of 10 nM, and cells were imaged or treated 24 h after transfection. The siRNA constructs (ThermoFisher Scientific) included a non‐targeting control (Catalog #4390843) and a previously validated CRLS1 ‐targeting sequence (siRNA ID: s29306) (Ohlig et al , 2018 ; Yang et al , 2023 ). For PA treatment, cells were transfected into complete DMEM containing specified 50 μM PA complexed to BSA and analyzed 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…For silencing experiments, Lipofectamine RNAiMAX was used per manufactures' instructions for an siRNA final concentration of 10 nM, and cells were imaged or treated 24 h after transfection. The siRNA constructs (ThermoFisher Scientific) included a non‐targeting control (Catalog #4390843) and a previously validated CRLS1 ‐targeting sequence (siRNA ID: s29306) (Ohlig et al , 2018 ; Yang et al , 2023 ). For PA treatment, cells were transfected into complete DMEM containing specified 50 μM PA complexed to BSA and analyzed 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo experiments further confirmed that FLIPUS could alleviate ECM loss and chondrocyte apoptosis in a destabilization of the medial meniscus (DMM) mouse model through mitophagy mediated by FUNDC1, thereby exerting a protective effect on cartilage ( Ye et al, 2023 ). In addition, syntaxin 17 (STX17) ( Xu et al, 2023 ), FK506 binding protein 8 (FKBP8) ( Yoo et al, 2020 ), nucleotide-binding domain and leucine-rich repeat-containing family member X1 (NLRX1) ( Zhang Y. et al, 2019 ), prohibitin 2 (PHB2) ( Lai et al, 2023 ), cardiolipin (CL) ( Yang et al, 2023 ), thioredoxin-interacting protein (Txnip) ( Zhang S. et al, 2023 ), dual-specificity protein phosphatase 1 (DUSP1) ( Li R. et al, 2023 ), and other mitophagy-related receptors have also been shown to mediate mitophagy under stress conditions.…”
Section: Overview Of Mitophagymentioning
confidence: 99%
“…For silencing experiments, Lipofectamine RNAiMAX was used per manufactures' instructions for an siRNA final concentration of 10 nM, and cells were imaged or treated 24 hours after transfection. The siRNA constructs (ThermoFisher Scientific) included a non-targeting control (Catalog #4390843) and previously validated CRLS1 -targeting sequence (siRNA ID: s29306) (Ohlig et al , 2018;Yang et al , 2023) . For PA treatment, cells were transfected into complete DMEM containing specified 50 μM PA complexed to BSA and analyzed 24 hours after transfection.…”
Section: Mammalian Cell Culturementioning
confidence: 99%